Estrategias lúdicas de enseñanza de la lecto-escritura para estudiantes de segundo año de educación básica “15 de Noviembre”, de la ciudad de Quevedo año lectivo 2023-2024 - Malagón Quijije, Isabel María (2024)
The general objective of the research was to provide playful teaching strategies that promote the learning of reading and writing of children in the second year of basic education at the “15 de Noviembre” Basic Education School in the city of Quevedo, in the first quarter of the year. 2023-2024 school year, by developing an intervention proposal that improves the reading-writing performance of students. The applied methodology responds to a non-experimental design with a quantitative approach, of a basic descriptive-propositive type, and by applying the instruments to the study sample made up of 33 2nd year EGB students and 6 elementary school teachers, it was obtained as The result is that there is a relationship between the application of playful strategies and the improvement of students' literacy. Therefore, a plan structured by 8 sessions of psycho-educational recreational work that enhances the psychomotor skills and oral and written comprehension of the students was developed as an intervention proposal.